Promoting the Effective Use of AI in Learning: A Smart Student’s Perspective at Karl Kumm University, Vom - Dadi Jonathan Abba; Adamu Ahmed Yarma; Mafeng Jamima Dudari (Mikailalsys Journal of Advanced Engineering International, 2026)
Artificial intelligence (AI), with its capacity to support individualized learning, efficient research, and enhanced academic productivity, has become a disruptive force in higher education. However, limited understanding, low levels of digital literacy, and ethical concerns prevent many students from harnessing AI effectively. This study examines strategies for promoting the efficient and responsible use of AI in education from the perspective of “smart students” at Karl Kumm University, Vom. Using a mixed-methods design, data were collected from 200 undergraduate students through surveys and interviews to explore AI awareness, adoption patterns, perceived benefits, and perceived challenges. The findings indicate that students recognize AI’s potential to improve learning and engagement, yet its optimal use is constrained by inadequate technical skills, fears of over-reliance, and unresolved ethical issues. The study proposes practical interventions, including mentorship schemes, curriculum integration, structured training programs, and clear ethical use guidelines, to foster more responsible and effective adoption of AI in learning. Overall, the results provide actionable insights for higher education institutions seeking to leverage AI to improve academic outcomes and to cultivate an innovative, self-directed learning culture by enabling students to become discerning and competent AI users.